2022
DOI: 10.1111/jmwh.13413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Virtual Reality and Music Therapy on the Physiologic Parameters of Pregnant Women and Fetuses and on Anxiety Levels: A Randomized Controlled Trial

Abstract: Introduction Anxiety negatively affects pregnant women and their fetuses. It can cause misleading test readings in electronic fetal monitoring, affect the duration of the first stage of labor, and influence certain aspects related to childbirth. This study aimed to evaluate the effects of virtual reality and music therapy on anxiety levels, maternal and fetal physiologic parameters, and labor and birth outcomes. Methods A total of 343 full‐term pregnant women participated in a randomized controlled trial and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
(93 reference statements)
0
16
0
Order By: Relevance
“…In addition, two trials reported the effects of antenatal relaxation on postnatal stress, anxiety and depression using the Depression, Anxiety and Stress Scale (DASS) [ 32 , 34 ], three trials reported symptoms of maternal anxiety during labour and 24 hours postnatal using the Visual Analogue Scale for Anxiety (VAS-A) [ 54 , 55 , 61 ] and one trial reported anxiety using the pregnancy-related anxiety questionnaire [ 62 ]. Six trials reported on Apgar score [ 33 , 51 , 55 57 , 60 ], three trials reported on gestational age (GA) [ 51 , 58 , 60 ], six trials reported on mode of delivery [ 33 , 50 52 , 55 , 58 ], and four trials reported on duration of labour [ 50 , 52 , 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, two trials reported the effects of antenatal relaxation on postnatal stress, anxiety and depression using the Depression, Anxiety and Stress Scale (DASS) [ 32 , 34 ], three trials reported symptoms of maternal anxiety during labour and 24 hours postnatal using the Visual Analogue Scale for Anxiety (VAS-A) [ 54 , 55 , 61 ] and one trial reported anxiety using the pregnancy-related anxiety questionnaire [ 62 ]. Six trials reported on Apgar score [ 33 , 51 , 55 57 , 60 ], three trials reported on gestational age (GA) [ 51 , 58 , 60 ], six trials reported on mode of delivery [ 33 , 50 52 , 55 , 58 ], and four trials reported on duration of labour [ 50 , 52 , 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, virtual reality has been shown to be safe and possibly effective in treating FD via immersive audio‐visual experiences in one double‐blind RCT 214 . Virtual reality has already been trialled for other purposes during pregnancy such as alleviating anxiety and pain 215–217 . Thus far, there have been no reported adverse events.…”
Section: Management Of Pre‐existing Functional Dyspepsia In Pregnancymentioning
confidence: 99%
“…for other purposes during pregnancy such as alleviating anxiety and pain. [215][216][217] Thus far, there have been no reported adverse events.…”
Section: Non-pharmacological Therapies-future Technologiesmentioning
confidence: 99%
“…Several studies have shown that music therapy may help reduce nausea and vomiting, reduce pain, and improve mood (Brungardt et al, 2021;Doro et al, 2017;Estrella-Juarez et al, 2022;Wakiguchi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that music therapy may help reduce nausea and vomiting, reduce pain, and improve mood (Brungardt et al, 2021; Doro et al, 2017; Estrella‐Juarez et al, 2022; Wakiguchi et al, 2021). However, few data are available regarding the potential effects of music intervention in children and adults undergoing HSCT.…”
Section: Introductionmentioning
confidence: 99%